Exercise and Repeated Testing Improves Accuracy of Laser Doppler Assessment of Microvascular Function Following Shortened (1‐minute) Blood Flow Occlusion. (May 2016) - Tran, Brian D.; Chiu, Abraham; Tran, Charlene; Rogacion, Danica Rose; Tfaye, Nicole; Ganesan, Goutham; Galassetti, Pietro R.
Abstract: Objectives: To determine whether stability/accuracy of post‐occlusive LDF following shortened, one‐minute blood flow occlusion, increases in the post‐exercise state or by averaging multiple measurements. Methods: Six healthy adults (3F) underwent LDF eight times at rest and following exercise, assessing post‐occlusive (one‐minute occlusion) reactive hyperemia in the cutaneous microcirculation of the forefinger. Measured variables included: pre‐ and post‐occlusion steady‐state perfusion (Plat1, Plat2), maximum post‐occlusive perfusion (Max), PkT, and the ratio Max/Plat1. Results: Stability/accuracy of all variables improved performing measurements after exercise ( p  < 0.05 Plat 1, Plat 2, Max and Max/Plat1). PkT and Max/Plat 1 displayed the greatest accuracy at rest (26.6 ± 5.1% and 26.6 ± 4.4% average difference, %Diff, of single measurements from individual "true" means, respectively); for these variables, %Diff improved to 19.5 ± 5.3 and 17.6 ± 2.1, respectively, following exercise. Overall, averaging multiple measurements performed at rest also improved stability/accuracy in all variables. This improvement was comparable to that obtained with a single measurement following exercise. Conclusions: A standardized exercise stimulus prior to testing significantly improves stability/accuracy of LDF following shortened, one‐minute blood flow occlusion. Our results suggest the possibilities of broader applications of exercise to optimize measurements from a variety of skin perfusion methodologies.